1989
DOI: 10.4049/jimmunol.143.4.1223
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin-macrophage interaction: post-translational regulation of tumor necrosis factor expression.

Abstract: Thioglycollate-elicited murine peritoneal macrophages produce significant quantities of TNF 2 to 4 h after induction with bacterial endotoxin, LPS. However, macrophages exposed to a second LPS stimulus are refractory and the amount of TNF detected in these supernatants is reduced 10- to 50-fold. The acquisition of the refractory state in vitro or in vivo requires the continued presence of LPS for a minimum of 6 to 8 h, is optimal by 20 h, and is reversible. Refractory macrophages incubated for an additional 48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…LPS tolerance may be regulated at the translational (20) and posttranslational (46) levels, but most studies have demonstrated a decrease in transcripts for TNF in tolerant cells (11,21,31). In the present study, we have confirmed that LPS tolerance in Mono Mac 6 cells accompanies a decreased level of TNF protein and mRNA.…”
Section: Discussionsupporting
confidence: 85%
“…LPS tolerance may be regulated at the translational (20) and posttranslational (46) levels, but most studies have demonstrated a decrease in transcripts for TNF in tolerant cells (11,21,31). In the present study, we have confirmed that LPS tolerance in Mono Mac 6 cells accompanies a decreased level of TNF protein and mRNA.…”
Section: Discussionsupporting
confidence: 85%
“…Several stimuli, including β-glucan, Bacillus Calmette-Guérin (BCG) vaccine, and oxidized low-density lipoprotein (oxLDL), render macrophages to a trained state that enhances inflammatory responses when cells are subsequently exposed 2 of 20 to microbial components such as lipopolysaccharide (LPS) [3,4]. Conversely, tolerance is demonstrated when macrophages that were pre-exposed to LPS become less responsive to the same or similar stimuli in producing inflammatory cytokines [5]. The first level of tolerance is a general dampening of activation and signaling through transient (lasting hours) negative feedback mechanisms including the downregulation of receptors [6], expressing negative signaling regulators, such as A20 [7] and interleukin-1 receptor-associated kinase-M (IRAK-M) [8], and inducing repressive transcription factors, such as B cell leukemia-3 and nuclear factor-κB (NF-κB) p50 [9].…”
Section: Introductionmentioning
confidence: 99%